Certificateless signature scheme without bilinear pairings - Sheng-bao WANG; Wen-hao LIU; Qi XIE (Tongxin xuebao)
To solve the key escrow problem inherited in ID-based cryptography and the complex certificate management problem of traditional certification-based public key cryptosystem,Al-Riyami and Paterson proposed the novel concept of certificateless public key cryptography.Almost all existing certificateless signature schemes need bilinear pairings either during signature generation stage or the signature verification stage,and were proven secure only with stronger computational assumptions.A new certificateless signature scheme without pairings was proposed.The scheme is provably secure in the random oracle model(ROM)under the relatively weaker assumption,i.e.,the discrete logarithm assumption and is more efficient than the existing schemes.